Industrial Combination as Surveyed in Recent Literature - Homan, Paul T. (Quarterly Journal of Economics, 1930)
Introduction, 345.—Jones, 347.—Jenks and Clark, 348.—Watkins, 350.—Seager and Gulick, 355.—Levy, 360.—Fitzgerald, 361.—National Industrial Conference Board publications: Mergers in Industry, 363;—Mergers and the Law, 366.—Alsberg, 369.—Toulmin, 370.—Javits, 370.—Frederick, 371.—Conclusions: “the trust problem” a misnomer, 372; many questions still unanswered, 373.